Effect of Cobalt Oxide Substitution on Mechanical Behaviour and Elastic Properties of Bioactive Glass and Glass-Ceramics. Issue 1 (2nd January 2016) - Vyas, Vikash Kumar; Sampath Kumar, Arepalli; Singh, S. P.; Pyare, Ram
ABSTRACT: 45S5 bioactive glass and glass-ceramics have been used widely because of their bonding capability with hard and soft tissues. One of their major applications is as artificial bone graft. Therefore, they are promising materials in the field of biomedical application. They have inferior mechanical properties in comparison to cortical bone. The present paper reports preparation of cobalt oxide doped 45S5 bioactive glass. Doping of Co 2+ ion from 0-2.0 wt% CoO was done to replace Si 4+ ion and yield a non charge balanced bioglass. Addition of Co 2+ ion was expected to form Si-O-Co and P-O-Co linkages in the bioglass. Tg of bioglasses were determined by differential thermal analysis. Bioactive glassceramics were processed through controlled crystallization of glasses. The crystalline phases in bioactive glass-ceramics were identified using X-ray difractometry. Density, compressive and bending strengths were determined. Ultrasonic wave velocities of bioactive glass and glass-ceramics were measured to study Young's, shear, bulk moduli and Poisson's ratio of the samples. The results indicated that doping of CoO in 45S5 bioactive glass and glass-ceramics enhanced its density, compressive, bending strength and elastic properties. GRAPHICAL ABSTRACT: